Urban growth and management of the drinking water service in the town of Copoya, of Tuxtla Gutiérrez, Mexico - Mérida-Martínez, Yliana (2024)
Equitable and permanent access to public services is not always a priority for local management, especially in those territories and historically neglected populations. This contribution argues that in Copoya, a mostly ejido locality in the Metropolitan Zone of Tuxtla Gutiérrez, state and community service for drinking water supply is inefficient. The situation has worsened with urban growth and demand for land throughout the twentieth century. Interviews, field visits and press releases show that residents, due to the lack of water, look for alternatives such as purchasing pipes, backyard wells and untreated water systems. These alternatives do not solve the underlying issue and deepen their poverty and socio-territorial inequality. The article concludes that poor investment in projects does not allow a solution for the supply in the short and medium term.